Effects of Cerebrolysin on Hippocampal Neuronal Death After Pilocarpine-Induced Seizure - Kang, Dong Hyeon; Choi, Bo Young; Lee, Song Hee; Kho, A Ra; Jeong, Jeong Hyun; Hong, Dae Ki; Kang, Beom Seok; Park, Min Kyu; Song, Hong Ki; Choi, Hui Chul; Lim, Man-Sup; Suh, Sang Won (Frontiers in Neuroscience, 2020)
Epilepsy is one of the most common and severe brain diseases. The exact cause of epilepsy is unclear. Epilepsy often occurs following brain damage, such as traumatic brain injury (TBI) and ischemia. Cerebrolysin is a porcine brain peptide that is a unique neurotropic and neuroprotective agent. Cerebrolysin has been reported to increase neuroprotective effects after TBI, ischemia, and other CNS diseases. However, the effect of cerebrolysin on seizure are not known. Therefore, this study aimed to investigate the effects of neuropeptide cerebrolysin on neuronal death in the hippocampus after a seizure. To confirm the effects of cerebrolysin, we used a pilocarpine-induced seizure animal model. Cerebrolysin (2.5 ml/kg, i.p., once per day for 7 days) was immediately injected after a seizure induction. After 1 week, we obtained brain tissues and performed staining to histologically evaluate the potentially protective effects of cerebrolysin on seizure-induced neuronal death in the hippocampus. We found that cerebrolysin decreased hippocampal neuronal death after a seizure. In addition, an increase in brain-derived neurotrophic factor (BDNF) was confirmed through Western blot analysis to further support our hypothesis. Therefore, the present study suggests that the administration of cerebrolysin can be a useful therapeutic tool for preventing neuronal death after a seizure.